Curcumin Improves Epithelial Barrier Integrity of Caco-2 Monolayers by Inhibiting Endoplasmic Reticulum Stress and Subsequent Apoptosis. (6th October 2021) - Zhou, Xinxin; Ren, Mengting; Yang, Jinpu; Pan, Hanghai; Yu, Mosang; Ji, Feng
Abstract : Curcumin is a natural polyphenol and is supposed to possess antioxidant, anti-inflammatory, anticancer, and antiapoptotic properties. Although some studies have reported the therapeutic effects of curcumin on ulcerative colitis (UC), the specific mechanism remains unclear. An in vitro coculture model of Caco-2 and differentiated THP-1 cells was established. After administration of curcumin (10  μ M), Western blot analysis was performed to evaluate the protein levels of tight junction (TJ) proteins zonula occludens- (ZO-) 1 and claudin-1. Annexin V-APC/7-AAD assays and flow cytometry were conducted to assess Caco-2 cell apoptosis. The expression levels of oxidative stress and endoplasmic reticulum stress- (ERS-) related molecules were determined by Western blot analysis. Curcumin administration significantly upregulated ZO-1 and claudin-1 protein levels and reduced Caco-2 cell apoptosis. The protein levels of oxidative stress markers inducible nitric oxide synthase (iNOS) and γ H2AX and ERS-induced apoptosis-related molecules C/EBP homologous protein (CHOP) and cleaved caspase-12 were significantly downregulated upon curcumin treatment. Furthermore, curcumin administration greatly blocked the protein kinase-like endoplasmic reticulum kinase- (PERK-) eukaryotic translation initiation factor 2 α - (eIF2 α -) activating transcription factor 4- (ATF4-) CHOP signaling pathway. Curcumin enhanced intestinal epithelial barrier integrity in the in vitro coculture model by upregulating TJ protein expressions and reducing intestinal epithelial cell apoptosis. The potential mechanisms may be suppression of ERS and subsequent apoptosis.